PEMBENTUKAN OMNIBUS LAW DALAM NEGARA DEMOKRASI DI INDONESIA - Afdhal afdhal (Muhammadiyah Makassar University, 2023)
ABSTRACTThe Omnisbus Law is a concept that was born from an idea that the laws and rules that are used as the foundation that regulate all activities of people's lives can be simplified and do not overlap in their application. The Omnibus Law in the Job Creation Law cluster was created in the context of simplifying licensing, facilitating doing business, facilitating, empowering and protecting MSMEs as well as increasing investment in government projects. The Omnibus Law is a device that is expected to create legal certainty for every element and layer of society.The scientific method in compiling this research is normative juridical with a statute approach and a conceptual approach. This method is carried out by collecting data that is classified and measured objectively on the basis of concepts, principles and laws in a comprehensive manner.In fact, the omnibus law is a product of the government which is still being debated because the paradigm of a democratic state requires the approval of the people. Law Number 6 of 2023 concerning the Stipulation of Government Regulations in lieu of Law Number 2 of 2022 concerning Job Creation to become a government breakthrough law which is expected to answer the phenomenon of hyper regulation. Regulation as a product of the Legislature is the implementation of the will of the people within the framework of political democracy. The ideals of the state are a collection of the aspirations of the people with the spirit of nationalism as a common pact and the rights and obligations of the state as emperor and regulator.Keywords: Omnibus Law, Democratic State, Indonesia